Tinjauan Efektivitas Kanal Sinrijala Pada Jalan Sukaria dalam Pengendalian Banjir Kota Makassar - Sardinar, Tyas Maulida; Yusuf, Andi Rumpang; Cangara, Satriawati (Program Studi Teknik Sipil Universitas Bosowa, 2024)
Flooding is a seasonal threat that occurs when water overflows from existing channels and inundates the surrounding area. Floods are the most frequent and most detrimental natural threat. Sinrijala Canal is a channel that drains water from the Pettarani region to the sea through the Pannampu Canal with a length of 2.36 km. The canal serves as an urban drainage and as the main base for flood control. The method used in this study is quantitative method. This research method can be done by collecting data and processing data so as to produce data that can solve research problems. Sinrijala's current drainage condition does have several problems, especially in the physical building. The flatness of the channel base and the reduced carrying capacity of the channel are caused by sedimentation. Therefore, handling is needed in the form of normalization activities in the form of dredging regularly and periodically. The channel discharge in the Sinrijala Canal is smaller than the puddle discharge so that the capacity of the canal drainage channel cannot drain or accommodate the amount of inundation in rainy conditions so that there is an overflow of 313.31 m3 / second. Sinrijala canals are declared ineffective for flood control because the flood discharge exceeds the discharge capacity that can be accommodated by the canal channel.